Preferensi Aedes aegypti Meletakkan Telur pada Berbagai Warna Ovitrap di Laboratorium - Made Agus Nurjana; Ade Kurniawan (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Dengue Haemograffic fever is a vector borne disease which caused outbreaks and death. There is no applied vaccine until now, so the effort of prevention and control is to terminate chain of infection mosquito breeding. Factors which influenced the female mosquitoe to lay their eggsare type of container, color, water, temperature, water source, humidity and environment condition. This study was conducted to determine the preferences of Ae. aegypti mosquitoes to lay aggs in various colors ovitrap in the laboratory of Balai Litbang P2B2 Donggala, January until March 2015. Three repetitions with plastic cup black, blue, white, yellow and pink have been performed with water and filter pappers. 30 mosquitoes blood saturation included in the containers with various colors. The result showed that most of female mosquito laid their eggs in plastic cup black (53,2%). ANOVA analysis showed that the diversity of colors ovitrap produce different the number of eggs Ae. aegypti in each type of countainer color. It is recommended to use black ovitrap for controling populations of Ae, aegypti in environment with regular monitoring.